A temática ambiental no curso de graduação de ciências contábeis: um enfoque a ambientalização curricular. - Alexandre, Elimar Rodrigues (2014)
Since the 1970s, different education sectors have developed proposals and researches about education for sustainability, but in the field of universities, this is an issue that only started to be discussed in the 1990s. On a global scale, in 2001, a group of eleven universities from seven different countries formed a group called ACES Network ¿ Curriculum Greening in Higher Education, presenting the creation of proposals and researches that treated about the Greening Curriculum issue. The ACES Network proposed ten features that a curriculum must present in order to be green or environmentalized and since that referential milestone several projects have been developed at the participant universities aiming to produce knowledge about the process. Considering those premises, the main objective of this research is understanding how the Accounting Sciences degree course of a Higher Education Institute in the Metropolitan Area of Baixada Santista, São Paulo State, embodies environmental issues on its curriculum. The data of the research were obtained through documental analysis of the curriculum evolution and project; from lesson plans of the subjects of the Accounting Sciences course and from the answers of the surveys sent to professors and students. Data were analyzed through the Discourse of the Collective Subject technique based on Lefevre and Lefevre. The results show that the level of Greening Curriculum of the researched Accounting Sciences course is still far from current proposals, even though there are some short initiatives on this path on the part of professors. The environmental issues found on the researched curriculum were definitions about accounting and the importance of the environmental liability accounts; soil recovery; legal questions about pollution and their reflexes on Accounting. About the ten features of an environmentalized curriculum, they were found in only one subject of the course, such as: commitment to the changes in the relations between society and nature; complexity; local-global-local context; consideration of human being in the construction of knowledge; attention to cognitive and affective values, ethical and aesthetic aspects; methodological adjustment and democratic reflection and participation spaces. To the majority of the students the environmental issues are important for the education of the Accountant to serve the labor market. Along this work, some paths to embodiment of environmental issues on the curriculum projects and reflections about the Greening Curriculum presence, were pointed: treating Social Balance, which is a tool that Accounting has to identify the level of socioenvironmental responsibility of organizations, as specific discipline or part of another discipline; inserting the curricular component named Environmental Accounting and the discipline Social Responsibility in the curricular matrix of the course; developing and applying a conceptual model for disclosure of economic financials aspects of events and transactions with environmental intent, viable for the Accounting Sciences course and aiming to demonstrate initiatives and activities which are implemented within the scope of environment protection.